Resist underlayer film formation method and pattern formation method

A resist underlayer film formed using a polymer composition without hydroxyl groups and specific organic groups, combined with heat and plasma treatment, addresses the challenges of insufficient dry etching resistance and planarization in semiconductor manufacturing, enabling precise pattern transfer.

JP2025010495APending Publication Date: 2025-01-21SHIN ETSU CHEMICAL CO LTD

Patent Information

Application Number
JP2024095214
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-07
Filing Date
2024-06-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Conventional resist underlayer films used in semiconductor manufacturing face challenges with insufficient dry etching resistance and planarization, especially as patterns become finer, leading to issues like pattern collapse and imperfect pattern transfer.

Method used

A method for forming a resist underlayer film using a polymer composition that does not contain hydroxyl groups or specific organic groups, subjected to heat treatment and plasma irradiation, to enhance dry etching resistance and planarization.

Benefits of technology

The method results in a resist underlayer film with superior dry etching resistance and excellent planarization properties, enabling precise transfer of fine patterns on substrates without defects such as voids or peeling, particularly suitable for advanced semiconductor manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010495000001_ABST
    Figure 2025010495000001_ABST
Patent Text Reader

Abstract

To provide a resist underlayer film formation method capable of forming a resist underlayer film exhibiting excellent dry etching resistance.SOLUTION: A resist underlayer film formation method for forming a resist under layer film on a substrate includes a step (i) of coating a composition for resist underlayer film formation containing a polymer (A) and an organic solvent onto the substrate and obtaining a coating film, and subjecting the coating film to heat treatment at a temperature of 100°C or higher and 800°C or lower from 10 seconds to 7,200 seconds and curing the coating film, to form an underlayer film precursor film, and a step (ii) of curing the underlayer film precursor film by plasma irradiation, to form a resist underlayer film, wherein as the polymer (A), an aromatic ring-containing resin containing no hydroxyl group and organic group represented by the following general formula (1) in a repeating unit constituting the polymer is used.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for forming a resist underlayer film and a method for forming a pattern, and more particularly to a method for forming a resist underlayer film that can be used for fine patterning by a multilayer resist method in a semiconductor device manufacturing process, and a method for forming a pattern using the resist underlayer film. [Background technology]

[0002] As LSIs become more highly integrated and faster, pattern dimensions are becoming finer. Lithography technology has achieved the formation of finer patterns by shortening the wavelength of light sources and selecting appropriate resist compositions to match them, in line with this trend. The core of this technology is a positive photoresist composition used in a single layer. This single-layer positive photoresist composition has a skeleton in the resist resin that is resistant to dry etching using chlorine- or fluorine-based gas plasma, and also has a switching mechanism that dissolves the exposed parts, forming a pattern by dissolving the exposed parts, and then using the remaining resist pattern as an etching mask to dry etch the substrate to be processed.

[0003] However, when the thickness of the photoresist film used is made finer, that is, when the pattern width is made smaller, the resolution performance of the photoresist film is reduced, and when an attempt is made to develop the photoresist film into a pattern using a developer, the so-called aspect ratio becomes too large, resulting in problems such as pattern collapse. For this reason, photoresist films have been made thinner as patterns become finer.

[0004] On the other hand, in the processing of a substrate to be processed, a method is usually used in which a photoresist film on which a pattern is formed is used as an etching mask to process the substrate by dry etching, but in reality, there is no dry etching method that can obtain perfect etching selectivity between the photoresist film and the substrate to be processed. Therefore, there is a problem that the photoresist film is also damaged and collapsed during processing of the substrate, and the resist pattern cannot be accurately transferred to the substrate to be processed. Therefore, with the miniaturization of patterns, a higher dry etching resistance has been required for the resist composition. However, on the other hand, in order to increase the resolution, a resin with low light absorption at the exposure wavelength has been required for the resin used in the photoresist composition. Therefore, as the exposure light has become shorter in wavelength from i-line to KrF and ArF, the resin has also changed to novolac resin, polyhydroxystyrene, and resin with an aliphatic polycyclic skeleton. However, in reality, the etching speed under dry etching conditions during substrate processing has become faster, and recent photoresist compositions with high resolution tend to have weaker etching resistance.

[0005] For this reason, it has become necessary to dry etch the substrate to be processed using a thinner photoresist film with a weaker etching resistance, and securing the materials and processes for this processing step has become an urgent need.

[0006] One method for solving such problems is the multi-layer resist method, in which a resist intermediate film having a different etching selectivity from a photoresist film (i.e., a resist upper layer film) is interposed between the resist upper layer film and a substrate to be processed, a pattern is obtained in the resist upper layer film, and the resist upper layer film pattern is used as a dry etching mask to transfer the pattern to the resist intermediate film by dry etching, and the resist intermediate film is further used as a dry etching mask to transfer the pattern to the substrate to be processed by dry etching.

[0007] One of the multilayer resist methods is a three-layer resist method that can be performed using a general resist composition used in a single-layer resist method. In this three-layer resist method, for example, an organic film made of novolac resin or the like is formed on a substrate to be processed as a resist underlayer film, a silicon-containing resist intermediate film is formed on the organic film as a resist intermediate film, and a normal organic photoresist film is formed on the organic film as a resist upper layer film. When dry etching is performed using fluorine-based gas plasma, the organic resist upper layer film has a good etching selectivity to the silicon-containing resist intermediate film, so that the resist upper layer film pattern can be transferred to the silicon-containing resist intermediate film by dry etching using fluorine-based gas plasma. According to this method, even if a resist composition that is difficult to form a pattern with a sufficient film thickness for directly processing a substrate to be processed or a resist composition that does not have sufficient dry etching resistance for processing a substrate is used, a pattern can be transferred to the silicon-containing resist intermediate film (resist intermediate film), and then, by performing pattern transfer by dry etching using oxygen-based or hydrogen-based gas plasma, a pattern of an organic film (resist underlayer film) made of novolac resin or the like that has sufficient dry etching resistance for processing a substrate can be obtained. As the above-mentioned resist underlayer film, many films are already known, for example, the one described in Patent Document 1.

[0008] On the other hand, in recent years, the miniaturization of DRAM memories has accelerated, and the need for a resist underlayer film having further improved dry etching resistance and excellent filling and planarization properties has increased. As a coating-type organic underlayer film material having excellent filling and planarization properties, for example, the one described in Patent Document 2 has been reported, but in terms of application to the latest generation, there are concerns about dry etching resistance, and the application limit of conventional coating-type organic underlayer film materials is approaching.

[0009] In response to the above problem, Patent Document 3 reports that the etching resistance during substrate processing is improved by irradiating the resist underlayer film with plasma or electron beam. However, the resist underlayer film used in the above examples often contains a resin or compound containing a hydroxyl group or a propargyl group, and crosslinking reactions also proceed competitively during plasma or electron beam irradiation, so it is expected that the modification of the resist underlayer film is insufficient. In addition, oxygen atoms remain in the film, which is considered to be undesirable from the viewpoint of etching resistance. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2004-205685 A [Patent Document 2] JP 2017-119671 A [Patent Document 3] JP 2020-183506 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a resist underlayer film forming method capable of forming a resist underlayer film that exhibits extremely superior dry etching resistance compared to conventional organic underlayer film materials, and a pattern forming method using the resist underlayer film forming method. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention provides a method for forming a resist underlayer film on a substrate, comprising the steps of: (i) coating the substrate with a composition for forming a resist underlayer film, the composition including (A) a polymer and an organic solvent, to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. or more and 800° C. or less for 10 to 7,200 seconds to harden the coating film, thereby forming an underlayer film precursor film; (ii) curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film; Including, The present invention provides a method for forming a resist underlayer film, characterized in that the polymer (A) is an aromatic ring-containing resin that does not contain a hydroxyl group or an organic group represented by the following general formula (1) in the repeating units that constitute the polymer: [ka] (In the above general formula (1), p is 0 or 1, and * is a bond.)

[0013] Such a method for forming a resist underlayer film makes it easy for the film to be modified by plasma irradiation, and can provide a resist underlayer film with excellent dry etching resistance. When the resist underlayer film contains a hydroxyl group or an organic group represented by the above general formula (1), the thermal curing proceeds actively, so that the number of active sites that are modified by plasma irradiation in the film decreases, which is not preferable.

[0014] It is preferable to use the above-mentioned (A) polymer, in which the above-mentioned aromatic ring-containing resin contains a structure selected from the group consisting of structures represented by the following formula (1-1). [ka]

[0015] By using a resin containing the above structure, the film is more easily modified by plasma exposure, and a resist underlayer film having even better dry etching resistance can be provided.

[0016] The polymer (A) preferably has any one of structural units represented by the following general formulae (A-1), (A-2), (A-3), (A-4) and (A-5). [ka] (In the general formula (A-1), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1) above.) [ka] (In the general formula (A-2), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1), and Ar2 is a fused aromatic ring different from Ar1, and is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1).) [ka] (In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.) [ka] (In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.) [ka] (In the general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms that does not contain a hydroxyl group or an organic group represented by the general formula (1), and each of Ar3 and Ar4 represents an unsubstituted benzene ring or naphthalene ring.)

[0017] By using a composition containing a resin having any one of the structural units represented by the above general formulas (A-1) to (A-5), it is possible to further improve the dry etching resistance after plasma exposure.

[0018] The (A) polymer preferably has a molecular weight of 300 to 5,000 in terms of polystyrene as determined by gel permeation chromatography.

[0019] A method for forming a resist underlayer film using a composition for forming a resist underlayer film containing a resin having a weight average molecular weight in such a range can suppress outgassing during baking without impairing solubility in organic solvents.

[0020] The composition for forming a resist underlayer film further comprises (C) a crosslinking agent, (D) a surfactant, (E) an acid generator, and (F) Plasticizer It is preferable to use one containing one or more of the above.

[0021] By using a composition for forming a resist underlayer film containing the above additive, it becomes possible to adjust various physical properties required when used to form a resist underlayer film, such as coatability, dry etching resistance, and filling / planarization characteristics, within an appropriate range.

[0022] In this case, it is preferable to use a crosslinking agent having a structure represented by the following general formula (C-1) as the (C) crosslinking agent. [ka] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2).) [ka]

[0023] When the composition contains a crosslinking agent having a structure represented by the above general formula (C-1), the resist underlayer film after plasma exposure can provide excellent film thickness uniformity.

[0024] In the step (ii), the plasma irradiation can be carried out in an atmosphere of N2, NF3, H2, a fluorocarbon, a rare gas, or a mixture of any of these.

[0025] By using the above-mentioned method for curing the resist underlayer film, it is possible to provide a resist underlayer film that exhibits excellent dry etching resistance compared to a curing method involving heating alone.

[0026] In the step (i), the heat treatment can be carried out in an atmosphere having an oxygen concentration of 1% or more and 21% or less.

[0027] By using such a method, the reactive sites of the resin in the resist underlayer film precursor film can be activated, and the curing reaction caused by the plasma irradiation can be promoted.

[0028] Alternatively, in the step (i), the heat treatment may be carried out in an atmosphere having an oxygen concentration of less than 1%.

[0029] This method is useful because it can activate the reactive sites of the resin in the resist underlayer film precursor film and promote the curing reaction by plasma irradiation without causing deterioration of the substrate to be processed, even if the substrate to be processed contains a material that is unstable when heated in an oxygen atmosphere.

[0030] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) forming a resist underlayer film on a substrate to be processed by the method for forming a resist underlayer film of the present invention; (I-2) forming a resist intermediate film on the resist underlayer film; (I-3) forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern has been transferred as a mask; and (I-7) A step of processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed. The present invention provides a pattern forming method comprising the steps of:

[0031] According to the above pattern formation method, a resist underlayer film exhibiting excellent dry etching resistance can be used, so that a fine pattern can be formed with high precision on a substrate, which is a workpiece. Effect of the Invention

[0032] As described above, the method for forming a resist underlayer film of the present invention makes it possible to form a resist underlayer film that exhibits extremely superior dry etching resistance compared to conventional organic underlayer film materials.

[0033] Furthermore, according to the pattern forming method of the present invention, a fine pattern can be formed with high precision on a substrate, which is a workpiece.

[0034] Furthermore, the resist underlayer film forming method and the pattern forming method of the present invention are particularly suitable for use in a multi-layer resist process, including filling / flattening a substrate to be processed having steps and irregularities, and are extremely useful in fine patterning for manufacturing semiconductor devices. In particular, in a fine patterning process using a multi-layer resist method in a semiconductor device manufacturing process, even on a substrate to be processed having a portion that is difficult to fill / flatten, such as a dense portion of a high aspect ratio fine pattern structure represented by a DRAM memory that is becoming increasingly finer, it is possible to fill without causing defects such as voids or peeling, and a resist underlayer film with excellent flatness characteristics can be formed. In addition, it shows excellent etching resistance compared to conventional resist underlayer film forming methods, and its effect can be exerted, especially by plasma irradiation. Therefore, a fine pattern can be formed on a substrate to be processed with even greater precision. [Brief description of the drawings]

[0035] [Figure 1] FIG. 1 is an explanatory diagram of an example of the pattern forming method of the present invention (three-layer resist process). [Diagram 2] FIG. 2 is an explanatory diagram of a method for evaluating embedding characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] As described above, in a fine patterning process using a multilayer resist method, there has been a demand for the development of a pattern formation method capable of transferring a resist pattern to a substrate to be processed with higher accuracy, and a formation method capable of forming a resist underlayer film useful for such a pattern formation method.

[0037] In Patent Document 3, it is reported that plasma irradiation improves the dry etching resistance of the resist underlayer film during substrate processing. It is considered that plasma irradiation dissociates and recombines the carbon bonds of the resist underlayer film, reconstructing the film as a hardened film having a diamond-like carbon structure, which contributes to an increase in hardness and density. On the other hand, since the composition for forming the resist underlayer film used in the examples of Patent Document 3 contains a hydroxyl group and an organic group represented by the above general formula (1), it is expected that not only the dissociation and recombination of carbon bonds but also crosslinking reactions will occur competitively. Therefore, the present inventors thought that the film modification by plasma irradiation may not have progressed sufficiently.

[0038] The present inventors have been searching for a method for forming a resist underlayer film in which dissociation and recombination of carbon bonds actively occurs by plasma irradiation, and have been conducting intensive research. As a result, it has been found that a method for forming an underlayer film, which includes a step of forming an underlayer film precursor film by coating a composition for forming a resist underlayer film, which comprises an aromatic ring-containing resin ((A) polymer) not containing a hydroxyl group and an organic group represented by the above general formula (1) and an organic solvent, and curing the obtained coating film by subjecting it to a heat treatment for 10 to 7,200 seconds at a temperature of 100°C to 800°C, and a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film, can form a resist underlayer film that exhibits extremely excellent dry etching resistance compared to the conventional method for forming a resist underlayer film by plasma irradiation, and has completed the present invention.

[0039] That is, the present invention is a method for forming a resist underlayer film on a substrate, comprising the steps of: (i) coating the substrate with a composition for forming a resist underlayer film, the composition including (A) a polymer and an organic solvent, to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. or more and 800° C. or less for 10 to 7,200 seconds to harden the coating film, thereby forming an underlayer film precursor film; (ii) curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film; Including, The method for forming a resist underlayer film is characterized in that the polymer (A) is an aromatic ring-containing resin that does not contain a hydroxyl group or an organic group represented by the following general formula (1) in the repeating units constituting the polymer: [ka] (In the above general formula (1), p is 0 or 1, and * is a bond.)

[0040] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) forming a resist underlayer film on a substrate to be processed by the method for forming a resist underlayer film of the present invention; (I-2) forming a resist intermediate film on the resist underlayer film; (I-3) forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern has been transferred as a mask; and (I-7) A step of processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed. The pattern forming method is characterized by comprising the steps of:

[0041] The present invention will be described in detail below, but the present invention is not limited thereto.

[0042] <Method for forming resist underlayer film> The present invention provides a method for forming a resist underlayer film on a substrate, comprising the steps of: (i) coating the substrate with a composition for forming a resist underlayer film, the composition including (A) a polymer and an organic solvent, to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. or more and 800° C. or less for 10 to 7,200 seconds to harden the coating film, thereby forming an underlayer film precursor film; (ii) curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film; Including, The method for forming a resist underlayer film is characterized in that the polymer (A) is an aromatic ring-containing resin that does not contain a hydroxyl group or an organic group represented by the following general formula (1) in the repeating units constituting the polymer: [ka] (In the above general formula (1), p is 0 or 1, and * is a bond.)

[0043] Such a method for forming a resist underlayer film can form a resist underlayer film having excellent resistance to dry etching during substrate processing. More specifically, such a method for forming a resist underlayer film can form a resist underlayer film having excellent resistance to dry etching, which is easily modified by plasma irradiation.

[0044] The method for coating the composition for forming a resist underlayer film in the above step (i) is not particularly limited. The details of the composition for forming a resist underlayer film will be described later.

[0045] In the above step (i), the heat treatment (baking) temperature of the coating film is from 100° C. to 800° C., more preferably from 150° C. to 600° C., and even more preferably from 150° C. to 400° C. The baking time is in the range of 10 seconds to 7,200 seconds, and even more preferably from 30 seconds to 600 seconds.

[0046] By adjusting the baking temperature and time appropriately within the above range, it is possible to obtain planarization and filling characteristics suitable for the application, as well as hardening characteristics such as dry etching resistance and heat resistance. By performing heat treatment (baking) within the temperature range of 150°C to 400°C, the film contains many active sites where carbon bonds in the underlayer film precursor film are dissociated and recombined, which makes it easier to promote film modification by plasma irradiation, and therefore a resist underlayer film with excellent dry etching resistance can be formed. At a baking temperature of 100°C or higher, the residual solvent in the film can be reduced, and deterioration of film thickness uniformity due to plasma irradiation can be suppressed. At a baking temperature of 800°C or lower, thermal decomposition of the base resin can be suppressed, and a resist underlayer film with a small amount of sublimation can be provided. It is also possible to perform the heating treatment in multiple steps (step baking).

[0047] In the above step (i), the heat treatment can be carried out in an atmosphere having an oxygen concentration of 1% or more and 21% or less.

[0048] By using such a method, the reactive sites of the resin in the resist underlayer film precursor film can be activated, and the curing reaction caused by the plasma irradiation can be promoted.

[0049] Alternatively, in the above step (i), the heat treatment can be carried out in an atmosphere with an oxygen concentration of less than 1%.

[0050] The atmosphere during baking can be selected as necessary from either an oxygen-containing atmosphere such as air (oxygen concentration 1% to 21%) or an oxygen-free atmosphere such as nitrogen. For example, if the substrate to be processed is susceptible to air oxidation, substrate damage can be suppressed by forming a hardened film by performing heat treatment in an atmosphere with an oxygen concentration of less than 1%.

[0051] The plasma irradiation can be performed by a known method, for example, the method described in Japanese Patent No. 5746670, "Improvement of the wiggling profile of spin-on carbon hard mask by H2 plasma treatment" (J.Vac.Sci.Technol. B26 (1), Jan / Feb 2008, p67-71).

[0052] The RF discharge power is preferably 100 to 10,000 W, and more preferably 500 to 5,000 W.

[0053] Examples of gas atmospheres include rare gases such as N2, NF3, H2, and He, and fluorocarbons; more preferably, He, Ar, N2, Ne, NF3, H2, CF4, CHF3, CH2F2, CH3F, C4F6, and C4F8. Two or more of these gases may be mixed for use. The advantage of the present invention is that the effect of the present invention can be expected even when a gas atmosphere that does not contain O2 is used.

[0054] The plasma irradiation time can be selected from the range of, for example, 10 to 240 seconds, and the pressure can be appropriately selected.

[0055] In the above step (ii), the plasma irradiation is preferably carried out in an atmosphere of N2, NF3, H2, a fluorocarbon, a rare gas such as He, or a mixture of any of these.

[0056] From the viewpoint of productivity, particularly preferred gas atmospheres include He, Ar, N2, H2, and the like.

[0057] After the plasma irradiation, the resist underlayer film may be subjected to a heat treatment. When heating after the plasma irradiation, the heating conditions can be appropriately selected from the range of a heating temperature of 80 to 800°C (preferably 100 to 700°C, more preferably 200 to 600°C) and a heating time of 30 to 180 seconds (preferably 30 to 120 seconds). Without being bound by theory, it is believed that high-temperature heating after the plasma irradiation can bond dangling bonds and contribute to densification of the cured film (resist underlayer film).

[0058] The atmosphere during heating after plasma irradiation can be selected as necessary from either an oxygen-containing atmosphere such as air (oxygen concentration 1% to 21%) or an oxygen-free atmosphere such as nitrogen. For example, if the substrate to be processed is susceptible to air oxidation, substrate damage can be suppressed by forming a hardened film by performing heat treatment in an atmosphere with an oxygen concentration of less than 1%.

[0059] The irradiation device is not particularly limited as long as it is capable of irradiating plasma, and for example, Telius SP and Tactras Vigus manufactured by Tokyo Electron Co., Ltd. can be used. It is possible to select the device and set the conditions so that the effect of the present invention can be more significantly exhibited.

[0060] In the pattern forming method of the present invention using the resist underlayer film forming composition described in detail below, it is preferable to use a substrate to be processed having a structure or step having a height of 30 nm or more. The resist underlayer film forming composition used in the present invention has excellent filling / flattening properties, so that even if the substrate to be processed has a structure or step (unevenness) having a height of 30 nm or more, a flat resist underlayer film (cured film) can be formed. The height of the structure or step of the substrate to be processed is preferably 30 nm or more, more preferably 50 nm or more, and more preferably 100 nm or more. In the method of processing a stepped substrate having a pattern of the above height, by forming a resist underlayer film and filling / flattening it by the resist underlayer film forming method of the present invention, it is possible to make the film thickness of the resist intermediate film and resist top layer film formed thereafter uniform, which is very preferable, as it is easy to ensure the exposure depth margin (DOF) during photolithography.

[0061] <Composition for forming resist underlayer film> In the method for forming a resist underlayer film of the present invention, a composition for forming a resist underlayer film containing (A) a polymer and an organic solvent is used, and as the polymer, an aromatic ring-containing resin which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating units constituting the polymer is used. [ka] (In the above general formula (1), p is 0 or 1, and * is a bond.)

[0062] [(A) Polymer (resin)] By using, as the (A) polymer, an aromatic ring-containing resin that does not contain a hydroxyl group or an organic group represented by the general formula (1) in the repeating units constituting the polymer, modification of the resist underlayer film by plasma exposure is easily caused, and it is possible to form a resist underlayer film that has excellent etching resistance during substrate processing.

[0063] The above polymer (A) is preferably a resin containing a structure selected from the group consisting of structures represented by the following formula (1-1). [ka]

[0064] By containing the above-mentioned high carbon density fused aromatic ring, the resist underlayer precursor film is more likely to be modified by plasma exposure, making it possible to form a resist underlayer film with superior dry etching resistance during substrate processing.

[0065] The above polymer (A) is preferably a resin having at least one of the structural units represented by the following general formulas (A-1) to (A-5).

[0066] (Constituent units: A-1 and A-2) [ka] (In the general formula (A-1), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1) above.) [ka] (In the general formula (A-2), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1), and Ar2 is a fused aromatic ring different from Ar1, and is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1).)

[0067] A resin having any one of the structural units represented by the above general formulas (A-1) and (A-2) has a fused aromatic ring with a high carbon density introduced therein, and therefore, dissociation and recombination of carbon bonds is easily promoted by plasma exposure, making it possible to form a resist underlayer film having a diamond-like carbon structure.

[0068] Specific examples of the structures of Ar1 and Ar2 include the following structure (A-1a), but are not limited thereto. [ka] (In the above formula (A-1a), R A1 is a divalent organic group having 1 to 20 carbon atoms that does not contain a hydroxyl group or an organic group represented by the above general formula (1), or a hydrogen atom.

[0069] When Ar1 and Ar2 are polymers having any of the fused aromatic rings represented by the above general formula (A-1a), it is possible to prepare a composition for forming a resist underlayer film having excellent solvent solubility. Since the polymer has a fused aromatic ring with a high carbon density, dissociation and recombination of carbon bonds is easily promoted by plasma irradiation, and a resist underlayer film having a diamond-like carbon structure can be formed.

[0070] In the above formula (A-1a), R A1 is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms (not including a hydroxyl group or an organic group represented by the above general formula (1)), more preferably a hydrogen atom, an alkyl group having 1 to 20 carbon atoms (not including a hydroxyl group or an organic group represented by the above general formula (1)), a phenyl group, or a benzyl group, and further preferably a hydrogen atom.

[0071] The above Ar1 and Ar2 are the groups R A1 embedded image is preferable because it is possible to further improve the solvent solubility without deteriorating the dry etching resistance.

[0072] From the viewpoints of the solvent solubility and productivity of the (A) aromatic ring-containing resin, the following structures are particularly preferred among the structures represented by the above general formula (A-1a).

[0073] [ka] (In the above formula, R A1is a divalent organic group having 1 to 20 carbon atoms that does not contain a hydroxyl group or an organic group represented by the above general formula (1), or a hydrogen atom.

[0074] The polymer having the structure represented by the above (A-1) may be a copolymer having two types of repeating units represented by the following formula (A-1x). [ka] (In the above formula (A-1x), Ar1' is any one of naphthalene, anthracene, phenanthrene, and pyrene, and Ar2' has a structure different from Ar1' and is any one selected from the above formula (A-1a). a+b is 100, 30≦a≦99, and 1≦b≦70.)

[0075] In the formula (A-1x), Ar1' is any one of naphthalene, anthracene, phenanthrene, and pyrene, but from the viewpoint of easily promoting dissociation and recombination of carbon bonds during high-temperature treatment in a nitrogen atmosphere and being able to form an amorphous carbon-like film, naphthalene and anthracene are preferable, and anthracene is more preferable. In addition, in the formula (2), Ar2' has a structure different from Ar1', but when Ar1' is anthracene, from the viewpoints of etching resistance, solvent solubility, and productivity, Ar2' is preferably naphthalene, phenanthrene, or pyrene.

[0076] In the formula (A-1x), the ranges of a and b are 30≦a≦99 and 1≦b≦70, and from the viewpoint of etching resistance and solvent solubility, it is preferable that they are 50≦a≦80 and 20≦b≦50.

[0077] A polymer having two different repeating units arranged randomly, such as that represented by the above formula (A-1x), is preferred because it can further improve the solvent solubility.

[0078] In the above general formula (A-2), it is preferable that either Ar1 or Ar2 is anthracene. By including the anthracene structure, dissociation and recombination of carbon bonds are easily promoted by plasma irradiation, and a resist underlayer film having a diamond-like carbon structure can be formed.

[0079] The resin having the structural units represented by the above general formulas (A-1) and (A-1x) may have a terminal blocking group represented by the following general formula (W-1): Note that the following terminal blocking group is not included in the repeating units constituting the polymer.

[0080] [ka] (In the above formula (W-1), * represents a bond to the structural unit represented by the above formula (A-1) or formula (A-2), d represents an integer of 1 to 9, and e represents an integer of 0 to 2.)

[0081] By having such an end-capping group, the solvent solubility and substrate adhesion of the resin can be further improved.

[0082] In the above formula (W-1), d is an integer of 1 to 9, and e is an integer of 0 to 2. From the viewpoints of etching resistance, solvent solubility, and substrate adhesion, it is preferable that d is 1 or 2, and e is 0 or 1. When it is desired to improve etching resistance, it is preferable that d is small and e is large. When it is desired to improve solvent solubility / substrate adhesion, it is preferable that d is large and e is small.

[0083] The molecular weight of the polymer having the structural units represented by the general formulas (A-1) and (A-2) in terms of polystyrene as determined by gel permeation chromatography is preferably 300 to 5,000, more preferably 500 to 3,500. When it is 300 or more, the amount of sublimation can be suppressed, and deterioration of the film thickness uniformity can be suppressed. When it is 5,000 or less, the solvent solubility of the resin can be maintained and precipitation over time can be prevented, which is preferable from the viewpoint of storage stability. In addition, since the fluidity is excellent, excellent embedding properties and excellent flatness can be realized. In addition, outgassing during baking can be suppressed without impairing the solubility of the polymer in organic solvents.

[0084] [First method for producing polymer] A resin having the structure represented by formula (A-1) as a repeating unit can be obtained, for example, by a polycondensation reaction between a condensed aromatic ring compound represented by Ar1 and an aldehyde, as shown below, where Ar1 is the same as above.

[0085] [ka]

[0086] The condensed aromatic ring compounds or aldehyde compounds used in the polycondensation reaction may be used alone or in combination of two or more kinds, which can be appropriately selected and combined depending on the required properties.

[0087] The polycondensation reaction can be carried out in an organic solvent in the presence of an acid catalyst at room temperature or under cooling or heating as necessary. Examples of the acid catalyst to be used include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids, organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid, and Lewis acids such as aluminum trichloride, aluminum ethoxide, aluminum isopropoxide, boron trifluoride, boron trichloride, boron tribromide, tin tetrachloride, tin tetrabromide, dibutyltin dichloride, dibutyltin dimethoxide, dibutyltin oxide, titanium tetrachloride, titanium tetrabromide, titanium(IV) methoxide, titanium(IV) ethoxide, titanium(IV) isopropoxide, and titanium(IV) oxide.

[0088] Examples of the organic solvent used in the polycondensation reaction include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric triamide. These can be used alone or in combination of two or more.

[0089] Examples of the reaction method include a method of charging the condensed aromatic ring compound, the aldehyde compound, and the acid catalyst all at once, a method of dispersing or dissolving the condensed aromatic ring compound and the aldehyde compound, and then adding the acid catalyst all at once or diluting it with a solvent and adding it dropwise, or a method of dispersing or dissolving the acid catalyst, and then adding the condensed aromatic ring compound and the aldehyde compound all at once or diluting it with a solvent and adding it dropwise. After the reaction is completed, the composition for forming an organic film of the present invention may be used as it is, but in order to remove unreacted raw materials, acid catalyst, etc. present in the system, it may also be recovered by diluting with an organic solvent and then performing separation and washing.

[0090] The organic solvent used in the liquid separation washing is not particularly limited as long as it can dissolve the compound and separates into two layers when mixed with water. Examples of the organic solvent include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone; ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethyl cyclopentyl methyl ether; chlorine-based solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; and mixtures thereof.

[0091] The washing water used in the liquid separation washing may be what is usually called deionized water or ultrapure water. The number of washings may be one or more times, but washing ten or more times does not necessarily provide the effect of washing, so it is preferably about one to five times.

[0092] In order to remove unreacted raw materials or acidic components from the system during separation washing, washing may be performed with a basic aqueous solution. Specific examples of the base contained in the basic aqueous solution include alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.

[0093] Furthermore, in order to remove unreacted raw materials, metal impurities, or basic components from the system during separation washing, washing may be performed with an acidic aqueous solution. Specific examples of the acid contained in the acidic aqueous solution include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids, and organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.

[0094] The above-mentioned separation washing with a basic aqueous solution and an acidic aqueous solution may be performed either alone or in combination. From the viewpoint of removing metal impurities, the separation washing is preferably performed in the order of a basic aqueous solution and an acidic aqueous solution.

[0095] After the above-mentioned separation washing with the basic aqueous solution or acidic aqueous solution, washing with neutral water may be performed successively. The number of washings may be one or more times, but is preferably about 1 to 5 times. As the neutral water, the above-mentioned deionized water or ultrapure water may be used. The number of washings may be one or more times, but if the number of washings is too few, the basic components and acidic components may not be removed. Even if washing is performed 10 times or more, the effect of washing alone may not be obtained, so it is preferably about 1 to 5 times.

[0096] Furthermore, the reaction product after separation washing can be recovered as a powder by concentrating the solvent to dryness or crystallizing it under reduced pressure or normal pressure, but it can also be left in a solution state of a moderate concentration in order to improve operability when preparing an organic film-forming composition. The concentration at this time is preferably 0.1 to 50% by mass, more preferably 0.5 to 30% by weight. At such a concentration, the viscosity is unlikely to increase, so that the operability is prevented from being impaired, and the amount of solvent is not excessive, so that it is economical.

[0097] The solvent used in this case is not particularly limited as long as it can dissolve the polymer, and specific examples include ketones such as cyclohexanone and methyl-2-amyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono tert-butyl ether acetate. These can be used alone or in combination of two or more.

[0098] [Second method for producing polymer (alternative method 1)] The resin having the structure represented by formula (A-1) as a repeating unit can also be obtained by a polymerization reaction using a raw material represented by Ar1-CH2-X, as a second alternative production method, where Ar1 is the same as above, and X is a hydroxyl group, an alkoxy group having 1 to 4 carbon atoms, or a halogen group.

[0099] [ka]

[0100] The polymerization reaction described above is a polymerization reaction that can obtain a polymer from a single monomer. In the polycondensation reaction of the first production method, a typical polymer is obtained by using two ordinary monomers A and B and undergoing an intermolecular dehydration reaction or the like to obtain a repeating unit derived from the monomers A and B, but the above-mentioned method for producing a polymer makes it possible to synthesize a homopolymer from one monomer. In the present invention, the second production method is preferred from the viewpoint of productivity.

[0101] [First method for producing polymers: Monomers alternately form repeating units] [ka]

[0102] [Second method for producing polymer (alternative method 1): homopolymer of monomer A only] [ka]

[0103] In the polymer synthesis reaction method shown above, when two types of monomers with different condensed aromatic rings (Ar1 and Ar2) are used as an example, a random polymer (A-1x) without a specific repeating unit can be synthesized by charging the monomers all at once, and after synthesizing a polymer with a monomer having Ar1 in the first stage, a polymer having a block structure can also be synthesized by further charging a monomer having Ar2 in two stages. These synthesis methods can be appropriately selected depending on the required performance, etc.

[0104] [ka]

[0105] [Two types of monomer: random type (batch charge)] [ka]

[0106] [Two types of monomer: block type (two-step preparation)] [ka]

[0107] The polymer represented by formula (A-1x) obtained by the above synthesis method contains two types of repeating units randomly, and therefore can provide a resin with excellent solvent solubility.

[0108] Furthermore, in the case of the second synthesis reaction method of the polymer shown above, an aromatic component Arx (Arx has no reactive unit) that can react with the monomer can be introduced as an end-capping unit either all at once or during the reaction. The method of introducing these end-capping groups can be appropriately selected depending on the reaction rate, etc. In the first polymerization method, it is possible to introduce only both ends due to reactivity, but when this polymerization method is used, one molecule of end-capping unit can be introduced into one polymer molecule, so when a polar group such as a hydroxyl group is introduced to adjust the film formability and adhesion when used as a resist underlayer film material by end-capping, performance can be improved with a minimum amount of introduction, which is advantageous in terms of etching resistance. On the other hand, when the repeating unit structure of the polymer contains a hydroxyl group or an organic group represented by the above general formula (1), a large number of crosslinking group components are contained in the polymer, so there is a risk that the dissociation / recombination of carbon bonds due to plasma irradiation and the hardening reaction will occur competitively, hindering the modification to a film with excellent dry etching resistance.

[0109] [End-capping: introduced during the reaction] [ka]

[0110] [End sealing: batch loading] [ka]

[0111] Examples of the aromatic component Arx include the following, and these aromatic rings may have a substituent such as a vinyl group, an ethynyl group, an ethynylphenyl group, an allyl group, a propargyl group, an aryl group, an allyloxy group, and a propargyloxy group. From the viewpoint of providing etching resistance and solvent solubility, the substituent preferably has a naphthalene ring, a fluorene structure, or a carbazole structure.

[0112] [ka]

[0113] [ka]

[0114] [ka]

[0115] [Third Method for Producing Polymer (Example of Method for Producing Resin Having Structure Represented by Formula (A-2) as Repeating Unit) (Alternative Method 2)] A polymer (resin) having the structure represented by the above formula (A-2) as a repeating unit can be obtained by a polymerization reaction using a condensed aromatic ring compound represented by Ar1 and a raw material represented by X-CH2-Ar2-CH2-X, as shown below.

[0116] [ka] (Ar1 and Ar2 are the same as above, and X is a hydroxy group, an alkoxy group having 1 to 4 carbon atoms, or a halogen group.)

[0117] The polymer obtained by the third production method (a resin containing the structure represented by formula (A-2) as a repeating unit) is a polymer having repeating units in which a condensed aromatic ring compound and X-CH2-Ar2-CH2-X are arranged alternately.

[0118] [Monomers A and B alternate to form repeating units] [ka]

[0119] The second and third synthesis reactions of the polymer are different from the first production method only in the monomers used, and the reaction method and recovery method can be similar to those described in the first production method.

[0120] (Constituent units: A-3 and A-4)

[0121] [ka] (In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.)

[0122] In the above general formula (A-3), from the viewpoint of availability of raw materials, R1 is preferably a hydrogen atom.

[0123] [ka] (In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.)

[0124] In the above general formula (A-4), from the viewpoint of availability of raw materials, R2 is preferably a hydrogen atom.

[0125] Resins having structural units represented by the above general formulae (A-3) and (A-4) have aromatic rings with high carbon density, and therefore dissociation and recombination of carbon bonds is easily promoted by plasma exposure, making it possible to form a resist underlayer film having a diamond-like carbon structure.

[0126] In addition, the polymer used in the present invention may be a resin containing both the structural units represented by the above general formulas (A-3) and (A-4), and may further contain a resin having a structural unit represented by the following general formula (A-4a).

[0127] [ka]

[0128] As the resins containing the above general formulae (A-3), (A-4) and (A-4a), there can be preferably mentioned those having a structure such as that of the following general formula (1C).

[0129] [ka] (In the above general (1C), a, b, and c are within the ranges of a+b+c=1, 0.5≦a≦0.9, and 0.1≦b+c≦0.5, respectively.)

[0130] In the above general formula (1C), a, b, and c are preferably within the ranges of a+b+c=1, 0.5≦a≦0.9, 0.1≦b+c≦0.5, and more preferably within the ranges of 0.7≦a≦0.9, 0.1≦b+c≦0.3.

[0131] The specific structure of the resin having the structures represented by the above general formulae (A-3) and (A-4) is not particularly limited as long as these structures are contained in the resin, and the resin may be a mixed composition of a resin having a structural unit represented by general formula (A-3) and a resin having a structural unit represented by general formula (A-4), or may be a copolymer of a resin having a structural unit represented by general formula (A-3) and a resin having a structural unit represented by general formula (A-4).

[0132] The polymer can be obtained by polymerizing polymerizable monomers by a known method. When obtaining a polymer, each monomer protected with a protecting group as necessary is polymerized, and then a deprotection reaction is performed as necessary, so that the polymer can be synthesized. The reaction method for obtaining the polymer is not particularly limited, and can be appropriately selected according to the reactivity of the monomers using methods such as radical polymerization and cationic polymerization.

[0133] When radical polymerization is used, a method is available in which monomers having polymerizable unsaturated bonds are mixed, and a radical initiator is added in a solvent to carry out heat polymerization, thereby obtaining a polymer. Polymerization conditions can be selected from a variety of options depending on the monomers used, the target molecular weight, and other factors. Specific examples of solvents used during polymerization include toluene, benzene, tetrahydrofuran, diethyl ether, dioxane, 2-butanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, cyclohexanone, γ-butyrolactone, ethyl acetate, and butyl acetate. Examples of polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2-azobis(2-methylpropionate), benzoyl peroxide, and lauroyl peroxide. In addition, thiols such as octanethiol and 2-mercaptoethanol may be added as chain transfer agents during polymerization. The polymerization reaction can be carried out by heating preferably to a temperature of from 40° C. to the boiling point of the reaction solvent. The reaction time is 0.5 to 100 hours, preferably 1 to 48 hours.

[0134] When cationic polymerization is used, a method is available in which a monomer having a polymerizable unsaturated bond is mixed and a cationic polymerization initiator is added to carry out polymerization, thereby obtaining a polymer. The polymerization conditions can be selected in various ways depending on the monomer used, the target molecular weight, and the like. Specific examples of the solvent used during polymerization include hexane, heptane, octane, toluene, methylene chloride, 1,2-dichloroethane, ethyl ether, and butyl ether. As a catalyst used as a cationic polymerization initiator, protonic acids such as hydrochloric acid, sulfuric acid, perchloric acid, trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, chlorosulfonic acid, and fluorosulfonic acid, and Lewis acids such as boron trifluoride, aluminum chloride, titanium tetrachloride, stannic chloride, and ferric chloride can be used. When a Lewis acid is used as a catalyst, a proton supply source such as an acid, water, or alcohol in an amount equivalent to that of the catalyst may be added because the cationic polymerization activity is improved. The polymerization reaction is not particularly limited as long as the reaction proceeds at a temperature at which the reaction proceeds, but is preferably carried out by heating to a temperature between -10°C and the boiling point of the reaction solvent. The reaction time is 0.5 to 100 hours, preferably 1 to 48 hours.

[0135] The method for obtaining the polymer is preferably cationic polymerization. In radical polymerization, a terminal structure containing heteroatoms other than carbon, such as oxygen and nitrogen, which deteriorate the etching resistance, is introduced into the polymer due to the radical initiator, but in cationic polymerization, such a disadvantage does not occur. Therefore, cationic polymerization is preferable as a method for obtaining the polymer from the viewpoint of etching resistance.

[0136] The molecular weight of the resin having any one of the structural units represented by the general formula (A-3) and (A-4) in terms of polystyrene as determined by gel permeation chromatography is preferably 300 to 5,000, more preferably 1,000 to 4,500, and even more preferably 2,000 to 4,000. When it is 300 or more, the amount of sublimation can be suppressed, and deterioration of the film thickness uniformity can be suppressed. When it is 5,000 or less, the solvent solubility of the resin can be maintained and precipitation over time can be prevented, which is preferable from the viewpoint of storage stability. In addition, since the fluidity is excellent, excellent embedding properties and excellent flatness can be realized. And, outgassing during baking can be suppressed without impairing the solubility of the polymer in organic solvents.

[0137] (Structural unit: A-5) [ka] (In the general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms that does not contain a hydroxyl group or an organic group represented by the general formula (1), and each of Ar3 and Ar4 represents an unsubstituted benzene ring or naphthalene ring.)

[0138] In the general formula (A-5), examples of the partial structure composed of Ar3 and Ar4 include the following: Among the following, fluorene and benzofluorene structures are preferred because of the ease of availability of raw materials.

[0139] [ka]

[0140] It is preferable that the polymer further has a partial structure represented by the following general formula (A-5a). [ka] (In the general formula (A-5a), Q1 is an alkyloxy group having 1 to 10 carbon atoms, or an organic group having one or more aromatic rings which may have a substituent other than a hydroxyl group and the organic group represented by the general formula (1), R1 is a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms which does not contain a hydroxyl group or an organic group represented by the general formula (1), and Ar3 and Ar4 are unsubstituted benzene rings or naphthalene rings.)

[0141] Examples of the organic group having one or more aromatic rings in Q1 in the general formula (A-5a) include the following, and these aromatic rings may have a substituent such as an alkyl group, an aryl group, an ethynylphenyl group, etc. From the viewpoint of imparting etching resistance and solvent solubility, the organic group preferably has a naphthalene ring, a fluorene structure, or a carbazole structure.

[0142] [ka]

[0143] [ka]

[0144] [ka]

[0145] In the present invention, the polymer preferably further has a partial structure represented by (A-5b).

[0146] [ka] (In the general formula (A-5b), Q2 represents a hydrogen atom or a monovalent organic group having 1 to 50 carbon atoms that does not contain a hydroxyl group or an organic group represented by the general formula (1), and Ar3 and Ar4 are as defined above.)

[0147] Examples of Q2 in the general formula (A-5b) include an alkyl group having 1 to 10 carbon atoms, or the following structure. When Q2 has an aromatic ring, the aromatic ring may have a substituent such as an alkyl group having 1 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, an ethynylphenyl group, or an aryl group. Among these, those having a naphthyl group are preferred from the viewpoint of providing etching resistance and solvent solubility.

[0148] [ka]

[0149] As a method for synthesizing the polymer, the method described in paragraphs

[0059] to

[0079] of Japanese Patent No. 7082087 can be used.

[0150] The molecular weight of the resin having the structural unit represented by the general formula (A-5) in terms of polystyrene as determined by gel permeation chromatography is preferably 300 to 5,000, more preferably 600 to 4,000. When it is 300 or more, the amount of sublimation can be suppressed, and deterioration of the film thickness uniformity can be suppressed. When it is 5,000 or less, the solvent solubility of the resin can be maintained and precipitation over time can be prevented, which is preferable from the viewpoint of storage stability. In addition, since the fluidity is excellent, excellent embedding properties and excellent flatness can be realized. And, outgassing during baking can be suppressed without impairing the solubility of the polymer in organic solvents.

[0151] [(B) Organic solvent] The organic solvent that can be used in the composition for forming a resist underlayer film is not particularly limited as long as it can dissolve the polymer (A), and is preferably one that can also dissolve the crosslinking agent, surfactant, acid generator, and plasticizer described below.

[0152] Specifically, for example, the solvents described in paragraphs

[0091] to

[0092] of JP 2007-199653 A can be added. More specifically, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, cyclohexanone, γ-butyrolactone, or a mixture containing one or more of these is preferably used.

[0153] The amount of the organic solvent to be added is desirably adjusted depending on the set film thickness of the resist underlayer film, but is usually within the range of 100 to 50,000 parts by mass per 100 parts by mass of the polymer (A).

[0154] [(B-1) High boiling point solvent] In addition, in the above-mentioned composition for forming a resist underlayer film, the (B) organic solvent may be used as a mixture of one or more organic solvents having a boiling point of less than 180 degrees and one or more organic solvents having a boiling point of 180 degrees or more (hereinafter referred to as "(B-1) high boiling point solvent").

[0155] Specific examples of organic solvents having a boiling point of less than 180 degrees include propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, and cyclohexanone.

[0156] The (B-1) high boiling point solvent is not particularly limited as long as it can dissolve each component of the composition for forming a resist underlayer film used in the present invention, and may be, for example, a hydrocarbon, an alcohol, a ketone, an ester, an ether, or a chlorine-based solvent. Specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-Hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerin, n-nonyl acetate, monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol-n-butyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol diacetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,Examples of the diethyl ester include 6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, and dibutyl adipate, and these may be used alone or in combination.

[0157] The (B-1) high boiling point solvent may be appropriately selected from the above, for example, according to the temperature at which the composition for forming a resist underlayer film is heat-treated. The (B-1) high boiling point solvent preferably has a boiling point of 180°C to 300°C, more preferably 200°C to 300°C. If the boiling point is in this range, there is no risk of the solvent volatilizing too quickly during baking (heat treatment) due to a boiling point that is too low, so that sufficient thermal fluidity can be obtained during film formation. In addition, if the boiling point is in this range, there is no risk of the solvent remaining in the film without volatilizing even after baking due to a boiling point that is too high, so that there is no risk of the solvent adversely affecting the film properties such as etching resistance.

[0158] When the high boiling point solvent (B-1) is used, the blending amount is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, per 100 parts by mass of the resin represented by the above general formula (A). Such a blending amount is preferable because there is no risk of the blending amount being too small to impart sufficient thermal fluidity during baking, or the blending amount being too large to remain in the film and lead to deterioration of film properties such as etching resistance.

[0159] [(C) Crosslinking agent] A crosslinking agent (C) can also be added to the composition for forming a resist underlayer film in order to enhance curability and improve dry etching resistance.

[0160] Specifically, the crosslinking agent (C) is preferably a compound having a structure represented by the following general formula (C-1). [ka] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2).) [ka]

[0161] By including the above-mentioned (C) crosslinking agent, the crosslink density and hardness of the resist underlayer film can be further improved without deteriorating the dry etching resistance of the composition for forming a resist underlayer film.

[0162] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the (C) crosslinking agent, calculated as polystyrene, by gel permeation chromatography, is preferably 1.00≦Mw / Mn≦1.25.

[0163] When the molecular weight dispersity of the crosslinking agent is as described above, the thermal fluidity of the composition for forming a resist underlayer film is good, and therefore when the crosslinking agent is blended into a resist underlayer film material, not only can the fine structure formed on the substrate be well embedded, but also a resist underlayer film that flattens the entire substrate can be formed.

[0164] Other (C) crosslinking agents are not particularly limited, and various known crosslinking agents can be widely used. Examples include melamine-based crosslinking agents, glycoluril-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, epoxy-based crosslinking agents, and phenol-based crosslinking agents (e.g., methylol or alkoxymethyl-type crosslinking agents of polynuclear phenols). When a crosslinking agent is added, the amount of the crosslinking agent is preferably 5 to 100 parts by mass, more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the resin represented by the above general formula (A).

[0165] Specific examples of the melamine-based crosslinking agent include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the glycoluril-based crosslinking agent include tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the benzoguanamine-based crosslinking agent include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the urea-based crosslinking agent include dimethoxymethylated dimethoxyethyleneurea, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the β-hydroxyalkylamide-based crosslinking agent include N,N,N',N'-tetra(2-hydroxyethyl)adipic acid amide. Specific examples of the isocyanurate crosslinking agent include triglycidyl isocyanurate and triallyl isocyanurate.Specific examples of the aziridine crosslinking agent include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline-based crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tertbutyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymer.Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.

[0166] Specific examples of polynuclear phenol-based crosslinking agents include compounds represented by the following general formula (C-2). [ka] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R3 is a hydrogen atom or a methyl group. q is an integer of 1 to 5.)

[0167] In the above general formula (C-2), Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. q is an integer of 1 to 5, and more preferably 2 or 3. When Q is a q-valent hydrocarbon group having 1 to 20 carbon atoms, Q is a q-valent hydrocarbon group obtained by removing q hydrogen atoms from a hydrocarbon having 1 to 20 carbon atoms. In this case, more specific examples of the hydrocarbon having 1 to 20 carbon atoms include methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane.

[0168] R3 in the above general formula (C-2) is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0169] By using the compound represented by the general formula (C-2) as the crosslinking agent (C), it is possible to improve the denseness of the film, which in turn makes it possible to further improve the heat resistance of the composition for forming a resist underlayer film.

[0170] Specific examples of the compound represented by the above general formula (C-2) include, but are not limited to, the following compounds. In the formula below, R3 is the same as above. From the viewpoints of curability, improved film thickness uniformity, and reduced sublimate, it is preferable that q=3 and R3 is a hydrogen atom or a methyl group, and in particular, hexamethoxymethylated products of triphenolmethane, triphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are preferred.

[0171] [ka]

[0172] [ka]

[0173] The above (C) crosslinking agent can be used alone or in combination of two or more. The content of the (C) crosslinking agent is preferably 5% by mass to 100% by mass, more preferably 10% by mass to 50% by mass, based on 100 parts by mass of the above (A) polymer. If the added amount is 5% by mass or more, the crosslinking reaction with the (A) polymer is promoted, and a dense film with excellent curability is formed, so that a resist underlayer film with good heat resistance, dry etching resistance, and film thickness uniformity can be formed. On the other hand, if the added amount is 100% by mass or less, the generation of sublimates due to the slowdown of the crosslinking reaction between the (A) polymer and the (C) crosslinking agent can be suppressed, and the generation of sublimates and the deterioration of film thickness uniformity can be reduced.

[0174] [(D) Surfactant] The resist underlayer film forming composition may contain a surfactant (D) to improve the coating property in spin coating. For example, the surfactants described in JP-A-2009-269953, paragraphs

[0142] to

[0147] may be used. The amount of the surfactant added is preferably 0.001 to 20 parts by mass, more preferably 0.01 to 10 parts by mass, based on 100 parts by mass of the polymer (A).

[0175] [(E) Acid generator] The resist underlayer film forming composition may contain (E) an acid generator that generates an acid by thermal decomposition or by light irradiation, and any of these may be added.Specifically, the materials described in paragraphs

[0061] to

[0085] of JP2007-199653A may be added, but are not limited thereto.

[0176] The acid generators may be used alone or in combination of two or more. When an acid generator is added, the amount of the acid generator added is preferably 0.05 to 50 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the polymer (A).

[0177] [(F) Plasticizer] In addition, the composition for forming a resist underlayer film may contain a plasticizer (F) in order to further improve the thermal fluidity. The plasticizer is not particularly limited, and various known plasticizers may be widely used. Examples of the plasticizer include low molecular weight compounds such as phthalates, adipic esters, phosphates, trimellitates, and citrates, and polymers such as polyethers, polyesters, and polyacetal polymers described in JP-A-2013-253227. When a plasticizer is added, the amount of the plasticizer is preferably 5 to 500 parts by mass, more preferably 10 to 200 parts by mass, relative to 100 parts by mass of the polymer (A).

[0178] In addition to the above, the resist underlayer film forming composition may contain an additive (flow promoter) for further improving the thermal flowability. The additive is not particularly limited as long as it contributes to improving the thermal flowability and imparts filling and flattening properties, but for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer having a weight loss rate of 40% or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000 is preferably used. This thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a).

[0179] [ka] (In the formula, R6 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. Y is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.)

[0180] [ka] (In the formula, R 6a is an alkyl group having 1 to 4 carbon atoms. a is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, which may have an ether bond; and n represents the average number of repeating units and is 3 to 500.

[0181] <Pattern formation method> The present invention also provides a pattern formation method by a two-layer resist process using the above-mentioned composition for forming a resist underlayer film, which comprises forming a resist underlayer film on a substrate to be processed by the resist underlayer film formation method of the present invention, forming a resist upper layer film on the resist underlayer film using a photoresist material, exposing the resist upper layer film to light and then developing it with a developer to form a pattern in the resist upper layer film, transferring the pattern to the resist underlayer film by dry etching using the resist upper layer film on which the pattern has been formed as a mask, and processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed.

[0182] The resist upper layer film in the two-layer resist process is preferably a photosensitive organometallic oxide film. The photosensitive organometallic oxide film exhibits resistance to etching by oxygen-based gas, so that in the two-layer resist process, the dry etching of the resist lower layer film using the resist upper layer film as a mask is preferably performed using an etching gas mainly containing oxygen-based gas.

[0183] In addition, the present invention provides a method for forming a pattern by a three-layer resist process using such a composition for forming a resist underlayer film, the method comprising the steps of: (I-1) forming a resist underlayer film on a substrate to be processed by the method for forming a resist underlayer film of the present invention; (I-2) forming a resist intermediate film on the resist underlayer film; (I-3) forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern has been transferred as a mask; and (I-7) A step of processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed. The present invention provides a pattern forming method comprising the steps of:

[0184] An example of a pattern forming method by a three-layer resist process will be described with reference to FIG. 1. First, as shown in FIG. 1(A), a resist underlayer film 3 is formed on a processable layer 2 of a processable substrate 1A including a support substrate 1 and a processable layer 2 formed thereon by the resist underlayer film forming method of the present invention, a resist intermediate film 4 is formed on the resist underlayer film 3 using a resist intermediate film material, and a resist upper layer film 5 is formed on the resist intermediate film 4 using a photoresist material. Subsequently, as shown in FIG. 1(B), an exposed portion 6 is formed in the resist upper layer film 5 by pattern exposure. Next, the exposed portion 6 is developed with a developer to form a resist upper layer film pattern 5a on the resist upper layer film 5 as shown in FIG. 1(C). Next, the silicon-containing resist intermediate film pattern 4a is transferred to the resist intermediate film 4 by dry etching using the resist upper layer film 5 on which the pattern 5a is formed as a mask as shown in FIG. 1(D). Next, the resist intermediate film 4 on which the pattern 4a is transferred is used as a mask as shown in FIG. 1(E), and a resist underlayer film pattern 3a is transferred to the resist underlayer film 3 by dry etching. Then, the layer 2 to be processed of the substrate 1A to be processed is processed using the resist underlayer film 3 on which the pattern 3a is formed as a mask, to form a pattern 2a on the substrate 1 to be processed as shown in FIG. 1(F).

[0185] Since the silicon-containing resist intermediate film in the above three-layer resist process exhibits resistance to etching by oxygen-based gas, it is preferable that the dry etching of the resist underlayer film in the above three-layer resist process is performed using the silicon-containing resist intermediate film as a mask, using an etching gas mainly composed of oxygen-based gas.

[0186] As the silicon-containing resist intermediate film in the above three-layer resist process, a polysiloxane-based intermediate film is also preferably used. By imparting an anti-reflection effect to the silicon-containing resist intermediate film, reflection can be suppressed. In particular, for 193 nm exposure, if a material containing many aromatic groups and having high etching selectivity with the substrate is used as the organic film, the k value becomes high and the substrate reflection becomes high, but by imparting absorption to the silicon-containing resist intermediate film so that the k value becomes appropriate, it is possible to suppress reflection and make the substrate reflection 0.5% or less. As the silicon-containing resist intermediate film having an anti-reflection effect, anthracene is preferably used for 248 nm or 157 nm exposure, and polysiloxane with a pendant light-absorbing group having a phenyl group or a silicon-silicon bond and crosslinked by acid or heat is preferably used for 193 nm exposure.

[0187] In addition, the present invention provides a pattern formation method by a four-layer resist process using such a resist underlayer film forming composition, which comprises the steps of forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method of the present invention, forming a silicon-containing resist intermediate film on the resist underlayer film using a silicon-containing resist intermediate film material, forming an organic antireflective coating (BARC) or an adhesion film on the silicon-containing resist intermediate film, forming a resist upper layer film on the BARC or adhesion film using a photoresist material, exposing the resist upper layer film to light and then developing it with a developer to form a pattern on the resist upper layer film, transferring the pattern to the BARC or adhesion film and the silicon-containing resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask, transferring the pattern to the resist underlayer film by dry etching using the silicon-containing resist intermediate film on which the pattern has been transferred as a mask, and processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed.

[0188] Alternatively, an inorganic hard mask may be formed instead of the silicon-containing resist intermediate film. In this case, at least a resist underlayer film is formed on a workpiece using the composition for forming a resist underlayer film of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film is formed on the resist underlayer film, a resist upperlayer film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the resist upperlayer film, the inorganic hard mask is etched using the resist upperlayer film on which the pattern has been formed as a mask, the resist underlayer film is etched using the inorganic hard mask on which the pattern has been formed as a mask, and the workpiece is etched using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the workpiece, thereby forming a semiconductor device circuit pattern on the substrate.

[0189] As described above, when an inorganic hard mask is formed on a resist underlayer film, a silicon oxide film, a silicon nitride film, and a silicon oxide nitride film (SiON film) can be formed by a CVD method, an ALD method, or the like. For example, methods for forming a silicon nitride film are described in JP-A-2002-334869 and WO-A-2004 / 066377. The thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. In addition, as the inorganic hard mask, a SiON film, which has a high effect as an anti-reflection film, is most preferably used. Since the substrate temperature during the formation of the SiON film is 300 to 500° C., the resist underlayer film needs to withstand a temperature of 300 to 500° C. The composition for forming the resist underlayer film used in the present invention has high heat resistance and can withstand high temperatures of 300 to 500° C., so that it is possible to combine an inorganic hard mask formed by a CVD method or an ALD method with a resist underlayer film formed by a spin coating method.

[0190] As described above, a photoresist film may be formed on the inorganic hard mask as a resist top layer, but an organic anti-reflective coating (BARC) or adhesion film may be formed on the inorganic hard mask by spin coating, and a photoresist film may be formed on top of that. In particular, when a SiON film is used as the inorganic hard mask, the two-layer anti-reflective coating of the SiON film and the BARC makes it possible to suppress reflection even in immersion exposure with a high NA exceeding 1.0. Another advantage of forming the BARC is that it has the effect of reducing the tailing of the photoresist pattern directly above the SiON film.

[0191] In the above pattern forming method, the resist upper layer film may be either positive or negative, and may be the same as a commonly used photoresist composition. The photoresist composition may contain metal atoms such as Sn, In, Ga, Ge, Al, Ce, La, Cs, Zr, Hf, Ti, Bi, Sb, and Zn. When forming the resist upper layer film using the above photoresist composition, it may be formed by spin coating or deposition processing using CVD or ALD.

[0192] When forming the resist top layer film by spin coating, the resist is pre-baked after coating, preferably at 60 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist pattern. The thickness of the resist top layer film is not particularly limited, but is preferably 10 to 500 nm, particularly preferably 20 to 400 nm.

[0193] When the resist top layer is formed by deposition processing by CVD or ALD, the resist composition is an EUV photosensitive metal oxide film, and the metal is selected from Sn, Zr, Hf, Ti, Bi, Sb, etc., among which Sn, which has excellent EUV photosensitivity, is preferred. The metal oxide-containing film may be a photosensitive organometallic oxide film such as an organotin oxide (e.g., haloalkyl Sn, alkoxyalkyl Sn, or amidoalkyl Sn). Some specific examples of suitable precursors include trimethyltin chloride, dimethyltin dichloride, methyltin trichloride, tris(dimethylamino)methyltin(IV), and (dimethylamino)trimethyltin(IV).

[0194] Metal oxide films may be deposited by PECVD or PEALD, for example using a Lam Vector® tool, with the Sn oxide precursor separated from the O precursor / plasma in the ALD embodiment. The deposition temperature is preferably in the range of 50° C. to 600° C. The deposition pressure is preferably between 100 and 6000 mTorr. The flow rate of the metal oxide-containing film precursor liquid (e.g., organotin oxide precursor) may be 0.01 to 10 cmm and the gas flow rate (CO2, CO, Ar, N2) may be 100 to 10000 sccm. The plasma power may be 200 to 1000 W per 300 mm wafer station using a high frequency plasma (e.g., 13.56 MHz, 27.1 MHz, or higher). The deposition thickness is preferably 100 to 2000 Å.

[0195] Examples of the exposure light include high energy rays with a wavelength of 300 nm or less, specifically, excimer lasers with wavelengths of 248 nm, 193 nm, and 157 nm, soft X-rays with wavelengths of 3 to 20 nm, electron beams, and X-rays.

[0196] The method for forming the pattern on the resist upper layer film is preferably photolithography with a wavelength of 5 nm or more and 300 nm or less, direct drawing with an electron beam, nanoimprinting, or a combination of these.

[0197] In the pattern forming method, the development method is preferably alkaline development or development using an organic solvent.

[0198] Next, etching is performed using the obtained resist pattern as a mask. In the three-layer resist process, etching of the silicon-containing resist intermediate film and the inorganic hard mask is performed using a fluorocarbon-based gas as a mask for the upper resist pattern. This forms a silicon-containing resist intermediate film pattern and an inorganic hard mask pattern.

[0199] Next, the resist underlayer film is etched using the silicon-containing resist intermediate film pattern or the inorganic hard mask pattern as a mask. The etching of the resist underlayer film is preferably carried out using an etching gas mainly containing an oxygen-based gas.

[0200] The next etching of the workpiece can also be done by a normal method, for example, if the workpiece is SiO2, SiN, or a silica-based low dielectric constant insulating film, etching is done mainly with fluorocarbon gases. When etching the substrate with fluorocarbon gases, the silicon-containing resist intermediate film pattern in the three-layer resist process is peeled off at the same time as the substrate is processed.

[0201] The resist underlayer film obtained by the method for forming a resist underlayer film of the present invention is characterized by excellent etching resistance when etching the workpiece.

[0202] The workpiece (substrate) is not particularly limited, and may be a substrate such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, or Al, or a substrate (support substrate) on which a workpiece layer is formed. As the workpiece layer, various low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, or Al-Si and their stopper films are used, and may be formed to a thickness of usually 50 to 10,000 nm, particularly 100 to 5,000 nm. When forming a workpiece layer, the substrate and the workpiece layer are made of different materials. EXAMPLES

[0203] The present invention will be specifically described below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. Note that, as for the molecular weight and dispersity, the weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene were determined by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent, and the dispersity (Mw / Mn) was determined.

[0204] Synthesis Example (A) Polymer Synthesis Polymers (A1) to (A13) were each synthesized by the following procedure. Compound group b: (b1) to (b10) shown below was used for synthesizing polymers (A1) to (A6) and polymers (A11) to (A13).

[0205] [ka]

[0206] [Synthesis Example 1] Synthesis of polymer (A1) [ka]

[0207] In a nitrogen atmosphere, 60.0 g of compound (b1) and 300 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C, and then 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 400 g of 1,2-dichloroethane was added, and then the insoluble matter was removed by filtration. The collected filtrate was washed six times with 200 g of pure water, and the organic layer was dried under reduced pressure. 150 g of THF was added to the residue to make a uniform solution, and then crystallized in 500 g of methanol. The precipitated crystals were separated by filtration, washed with 300 g of methanol and 300 g of diisopropyl ether in that order, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 33.2 g of polymer (A1).

[0208] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A1): Mw = 560, Mw / Mn = 2.43

[0209] [Synthesis Example 2] Synthesis of polymer (A2) [ka]

[0210] In a nitrogen atmosphere, 30.0 g of compound (b2), 22.2 g of compound (b3) and 300 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C, and then 55.0 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 24 hours. After cooling to room temperature, 400 g of 1,2-dichloroethane was added, and then the insoluble matter was removed by filtration. The collected filtrate was washed six times with 200 g of pure water, and the organic layer was dried under reduced pressure. 150 g of THF was added to the residue to make a uniform solution, and then crystallized in 500 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 45.6 g of polymer (A2).

[0211] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A2): Mw = 3560, Mw / Mn = 1.93

[0212] [Synthesis Example 3] Synthesis of polymer (A3) [ka]

[0213] In a nitrogen atmosphere, 30.0 g of compound (b1), 22.8 g of compound (b4) and 260 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C, and then 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then insoluble matter was removed by filtration. The collected filtrate was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 120 g of THF was added to the residue to make a uniform solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed with 300 g of methanol and 300 g of diisopropyl ether in that order, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 33.3 g of polymer (A3).

[0214] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A3): Mw=720, Mw / Mn=2.13

[0215] [Synthesis Example 4] Synthesis of polymer (A4) [ka]

[0216] In a nitrogen atmosphere, 30.0 g of compound (b1), 15.6 g of compound (b5) and 230 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C, and then 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then insoluble matter was removed by filtration. The collected filtrate was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 120 g of THF was added to the residue to make a uniform solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed with 300 g of methanol and 300 g of diisopropyl ether in that order, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 27.3 g of polymer (A4).

[0217] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A4): Mw=680, Mw / Mn=2.27

[0218] [Synthesis Example 5] Synthesis of polymer (A5) [ka]

[0219] In a nitrogen atmosphere, 60.0 g of compound (b1), 4.6 g of compound (b6) and 325 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C, and then 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then insoluble matter was removed by filtration. The collected filtrate was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 200 g of THF was added to the residue to make a uniform solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed with 300 g of methanol and 300 g of diisopropyl ether in that order, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 36.3 g of polymer (A5).

[0220] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A5): Mw=700, Mw / Mn=1.43

[0221] [Synthesis Example 6] Synthesis of polymer (A6) [ka]

[0222] In a nitrogen atmosphere, 60.0 g of compound (b4), 6.3 g of compound (b7) and 350 g of 1,2-dichloroethane were mixed and made into a homogeneous solution at an internal temperature of 60°C, and then 80.2 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and the organic layer was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 200 g of THF was added to the residue to make a homogeneous solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed with 300 g of methanol and 300 g of diisopropyl ether in that order, and the crystals were collected. The collected crystals were dried in a vacuum at 70°C to obtain 35.5 g of polymer (A6).

[0223] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A6): Mw=730, Mw / Mn=1.38

[0224] [Synthesis Example 7] Synthesis of polymer (A7) [ka]

[0225] In a nitrogen atmosphere, 3.8 g of methanesulfonic acid and 30 g of methylene chloride were mixed and homogenized at an internal temperature of 30°C, and then a mixture of 30.0 g of acenaphthylene and 60.0 g of methylene chloride was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 35°C for 24 hours. After cooling to room temperature, 300 g of toluene was added, washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 90 g of THF was added to the residue to make a homogenous solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 28.7 g of polymer (A7).

[0226] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A7): Mw=2400, Mw / Mn=1.93

[0227] [Synthesis Example 8] Synthesis of polymer (A8) [ka]

[0228] In a nitrogen atmosphere, 5.0 g of methanesulfonic acid and 30.0 g of methylene chloride were mixed and homogenized at an internal temperature of 30°C, and then a mixture of 30.0 g of indene and 60.0 g of methylene chloride was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 35°C for 24 hours. After cooling to room temperature, 300 g of toluene was added, washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 90 g of THF was added to the residue to make a homogenous solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 26.9 g of polymer (A8).

[0229] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A8): Mw=2500, Mw / Mn=1.83

[0230] [Synthesis Example 9] Synthesis of polymer (A9) [ka]

[0231] Under a nitrogen atmosphere, 37.5 g of propylene glycol monomethyl ether acetate (PGMEA) was stirred at 80°C, and then a mixture of 50.0 g of acenaphthylene and 82.5 g of PGMEA and a mixture of 3.8 g of dimethyl 2,2-azobis(2-methylpropionate) and 30.0 g of PGMEA were added simultaneously and separately over 2 hours. After further heating and stirring for 24 hours, the mixture was cooled to room temperature. The reaction solution was dropped into 750 g of methanol to crystallize a polymer. The precipitated crystals were separated by filtration and washed twice with 300 g of methanol to recover the crystals. The recovered crystals were vacuum dried at 70°C to obtain 48.3 g of polymer (A9).

[0232] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A9): Mw=4100, Mw / Mn=1.73

[0233] [Synthesis Example 10] Synthesis of polymer (A10) [ka]

[0234] In a nitrogen atmosphere, 5.7 g of methanesulfonic acid and 29.5 g of methylene chloride were mixed and homogenized at an internal temperature of 30°C, and then a mixture of 15.0 g of acenaphthylene, 6.9 g of indene, 7.6 g of 9-vinylcarbazole, and 59.0 g of methylene chloride was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 35°C for 24 hours. After cooling to room temperature, 300 g of toluene was added, washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 90 g of THF was added to the residue to make a homogeneous solution, and then crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 27.9 g of polymer (A10).

[0235] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (A10): Mw=4000, Mw / Mn=2.15

[0236] [Synthesis Example 11] Synthesis of polymer (A11) [ka]

[0237] Under a nitrogen atmosphere, 200 g of 1,2-dichloroethane was added to 30.0 g of compound (b8) to obtain a homogeneous solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added, and the mixture was reacted at an internal temperature of 70°C for 8 hours. After cooling to room temperature, 500 g of toluene was added, and the mixture was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to obtain a homogeneous solution, and the solution was crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were collected. The collected crystals were dried in a vacuum at 70°C to obtain 25.6 g of polymer (A11) represented by the above formula.

[0238] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC measurement, and the results were as follows: (A11): Mw = 2600, Mw / Mn = 1.68

[0239] [Synthesis Example 12] Synthesis of polymer (A12) [ka]

[0240] Under a nitrogen atmosphere, 2.75 g of compound (b7), 30.0 g of compound (b8) and 200 g of 1,2-dichloroethane were added to obtain a homogeneous solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added and reacted at an internal temperature of 70°C for 8 hours. After cooling to room temperature, 500 g of toluene was added, washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF was added to the residue to obtain a homogeneous solution, and then crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were collected. The collected crystals were vacuum dried at 70°C to obtain 25.4 g of polymer (A12) represented by the above formula.

[0241] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC measurement, and the results were as follows: (A12): Mw = 1420, Mw / Mn = 1.53

[0242] [Synthesis Example 13] Synthesis of polymer (A13) [ka] Under a nitrogen atmosphere, 100 g of 1,2-dichloroethane was added to 10.0 g of compound (b9) to obtain a homogeneous solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 4 hours. After that, the internal temperature was cooled to 50°C, and a mixture of 13.7 g of compound (b10) and 100 g of 1,2-dichloroethane, which had been homogenized in advance, was slowly dropped, and the internal temperature was raised to 70°C again to perform a reaction for 8 hours. After cooling to room temperature, 500 g of toluene was added, and the mixture was washed six times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF was added to the residue to obtain a homogeneous solution, and then crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were collected. The collected crystals were dried in a vacuum at 70°C to obtain 18.7 g of polymer (A13) represented by the above formula.

[0243] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC measurement, and the results were as follows: (A13): Mw = 2930, Mw / Mn = 1.61

[0244] [Synthesis of Comparative Compounds] The comparative compounds (R2), (R3) and (R4) were synthesized using the following compound group c: (c1) to (c6).

[0245] [ka]

[0246] [Comparative Synthesis Example 1] Synthesis of Comparative Compound (R1) [ka] Under a nitrogen atmosphere, 15.6 g of 2-phenylphenol, 19.1 g of 9-anthracenemethanol, 12.3 g of divinylbenzene, 30 g of cyclopentyl methyl ether (CPME), and 110 g of diethylene glycol dimethyl ether were added and stirred at room temperature to uniformly disperse. Then, 1.14 g of trifluorosulfonic acid was slowly added, and the mixture was stirred for another 5 minutes to obtain a uniform solution, after which the reaction was carried out for 4 hours in an oil bath at 140°C while removing the water generated from the reaction system. The mixture was cooled to room temperature, diluted with 250 g of CPME, transferred to a separatory funnel, washed four times with ultrapure water, and the organic layer was dried under reduced pressure. 120 g of CPME was added to the residue, and a polymer was crystallized with 500 g of hexane. The crystallized crystals were separated by filtration, washed twice with 200 g of hexane, and the crystals were collected. The collected crystals were dried in a vacuum at 70°C to obtain a comparative compound (R1). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R1): Mw=1960, Mw / Mn=1.57

[0247] [Comparative Synthesis Example 2] Synthesis of Comparative Compound (R2) [ka] In a nitrogen atmosphere, 80.0 g of epoxy compound (c1), 51.0 g of modifying agent (c2), and 600 g of 2-methoxy-1-propanol were added and made into a homogeneous solution at 100°C, after which 5.7 g of benzyltriethylammonium chloride was added and stirred at 120°C for 12 hours. The mixture was cooled to room temperature, 1,500 g of methyl isobutyl ketone was added, and the organic layer was washed five times with 300 g of pure water. The organic layer was dried under reduced pressure to obtain a comparative compound (R2).

[0248] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R2): Mw=900, Mw / Mn=1.04

[0249] [Comparative Synthesis Example 3] Synthesis of Comparative Compound (R3) [ka] Under a nitrogen atmosphere, 20 g of 9-fluorenone (c3), 230 g of 9,9-bis(4-hydroxyphenyl)fluorene (c4) and dichloromethane (1,040 g) were added and made into a homogeneous solution at 40°C. Trifluoromethanesulfonic acid (9 g) and 3-mercaptopropionic acid (0.6 g) dissolved in dichloromethane (20 g) were added and stirred at 40°C for 4 hours. The mixture was cooled to room temperature and the organic layer was washed five times with 300 g of pure water. The organic layer was dried under reduced pressure to obtain a comparative compound (R3).

[0250] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R3): Mw=680, Mw / Mn=1.26

[0251] [Comparative Synthesis Example 4] Synthesis of Comparative Compound (R4) [ka] In a nitrogen atmosphere, the comparative compound R3 (20 g) obtained in Comparative Synthesis Example 3, potassium carbonate (32 g), and acetone (62 g) were added and made into a homogeneous solution at 56°C, and then 3-bromo-1-propyne (28 g) was slowly added to the reactor and stirred at 56°C for 3 hours. The mixture was cooled to room temperature, and the excess potassium carbonate and salts were removed by filtration, and the precipitate was washed with acetone. The organic layer was washed five times with 300 g of pure water. The organic layer was dried under reduced pressure to obtain the comparative compound (R4).

[0252] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R4): Mw = 1,040, Mw / Mn = 1.38

[0253] [Comparative Synthesis Example 5] Synthesis of Comparative Compound (R5) [ka]

[0254] In a 200 mL flask, 15.2 g of acenaphthylene, 3.3 g of 4-hydroxystyrene, and 60 g of 1,2-dichloroethane as a solvent were added. 1 g of trifluoroboron was added as a polymerization initiator, and the mixture was heated to 60°C and reacted for 25 hours. 1 L of methanol and 500 g of water were added to the reaction solution to precipitate a polymer, and the resulting white solid was filtered and dried to obtain 12 g of a polymer (compound (R5) for comparison).

[0255] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R5): Mw=8800, Mw / Mn=1.82

[0256] [Comparative Synthesis Example 6] Synthesis of Comparative Compound (R6) [ka]

[0257] 41.2 g of tertiary alcohol (c6) and 160 g of methylene chloride were mixed. 19.2 g of methanesulfonic acid was slowly added dropwise and the mixture was heated under reflux for 8 hours. After cooling to room temperature, 250 g of toluene was added, washed with water, and concentrated under reduced pressure to obtain 37.6 g of a comparative compound (R6).

[0258] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the results were as follows: (R6): Mw=1850, Mw / Mn=1.26

[0259] [Synthesis Example: (C) Synthesis of Crosslinker] [Synthesis Example 15] Synthesis of compound (C1) [ka]

[0260] In a nitrogen atmosphere, 219g of bis(4-bromophenyl)ether and 1000mL of t-butyl methyl ether were cooled to -20℃, and 500mL of 2.67M n-butyllithium hexane solution was added, followed by stirring at -20℃ for 20 minutes. 229g of 9-fluorenone was added, and the mixture was gradually heated to room temperature and stirred at room temperature for 4 hours. Water was added to stop the reaction. After washing with water and concentrating under reduced pressure, hexane was added, and the resulting solid was filtered, washed with hexane, and dried under reduced pressure to obtain 293g of compound (C1). (C1): Mw=540, Mw / Mn=1.02

[0261] [Synthesis Example 16] Synthesis of compound (C2) [ka]

[0262] Under a nitrogen atmosphere, 30.0 g of compound (C1) and 172.8 g of 1-butanol were suspended at an internal temperature of 80°C. 16.8 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 100°C for 6 hours. After cooling in an ice bath to precipitate crystals, the precipitated crystals were separated by filtration, washed twice with 200 g of butanol, and washed three times with 200 g of diisopropyl ether, and then collected. The collected crystals were dried in a vacuum at 60°C to obtain 34.2 g of compound (C2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained. (C2): Mw=640, Mw / Mn=1.01

[0263] [Preparation of composition for forming resist underlayer film (UDL-1)] The polymer (A1) as a compound for forming a resist underlayer film was dissolved in a mixed solvent of propylene glycol monomethyl ether acetate (PGMEA) and cyclohexanone (CyHO) containing 0.5 mass % of a surfactant FC-4430 (manufactured by Sumitomo 3M Limited) in the ratio shown in Table 2. The obtained solution was filtered through a 0.02 μm membrane filter to prepare a composition for forming a resist underlayer film (UDL-1).

[0264] [Preparation of compositions for forming resist underlayer films (UDL-2 to 16) and compositions for forming resist underlayer films for comparative examples (UDL-1 to 6 for comparative examples)] Compositions for forming resist underlayer films (UDL-2 to 16) and compositions for forming resist underlayer films for comparative examples (UDL-1 to 6 for comparative examples) were prepared in the same manner as in the composition for forming resist underlayer films (UDL-1), except that the type and content of each component was as shown in Table 2. In Table 2, "-" indicates that the corresponding component was not used. The acid generator (TAG) represented by the following formula (E1) was used, and the flowability promoter represented by the following formula (G1) was used.

[0265] [Acid generator] The thermal acid generator (E1) used in the composition for forming the resist underlayer film is shown below. [ka]

[0266] [Flow enhancer] Table 1 shows the flowability promoter (G1) used in the composition for forming the resist underlayer film.

[0267] [Table 1]

[0268] [Table 2]

[0269] [Example 1 and Comparative Example 1: Evaluation of Dry Etching Resistance] Each of the resist underlayer film forming compositions (UDL-1 to 16, Comparative Example UDL-1 to 6) prepared above was applied onto a silicon substrate and baked at 250°C for 60 seconds. Thereafter, the film thickness from the center to the outer periphery of the substrate was measured to calculate the average film thickness (a [nm]). Next, etching was performed using CF4 gas under the following conditions using a Telius etching device manufactured by Tokyo Electron, and the film thickness b was measured. The film thickness etched in 1 minute was calculated as the etching rate A (nm / min) from the film thickness (film thickness a-film thickness b) etched using CF4 gas during a specified time. The results are shown in Table 3.

[0270] Separately from the above, each of the resist underlayer film forming compositions (UDL-1 to 16, Comparative Example UDL-1 to 6) was applied onto a silicon substrate and heated at 250°C for 60 seconds. Thereafter, plasma treatment was performed under the plasma treatment conditions described below to form a resist underlayer film, and the film thickness c was measured. Next, etching was performed using CF4 gas under the conditions described below using a Telius etching device manufactured by Tokyo Electron, and the film thickness d was measured. The film thickness etched in 1 minute was calculated as the etching rate B (nm / min) from the film thickness (film thickness c - film thickness d) etched using CF4 gas during a specified time.

[0271] The smaller the etching rate number, the better the etching resistance to CF4 gas.

[0272] The etching resistance of the cured film (resist underlayer film) that had been subjected to additional plasma treatment was compared with that of the underlayer film precursor film obtained by baking at 250°C, and the improvement in etching resistance due to the additional plasma treatment (etching rate A (nm / min) - etching rate B (nm / min)) was calculated.

[0273] The etching conditions are as follows. Dry etching conditions with CF4 gas Chamber pressure: 100mT RF power (top): 500W RF power (bottom): 400W CF4 gas flow rate: 300sccm Time: 30sec

[0274] Additional processing conditions (plasma processing) Each substrate was heated at 250° C. for 60 seconds and then subjected to plasma treatment under the following conditions using a Telius etching device manufactured by Tokyo Electron. Plasma treatment conditions Chamber pressure: 100mT RF Power (Top): 100W RF power (lower part): 3500W H2 gas flow rate: 200sccm Time: 20sec

[0275] [Table 3]

[0276] As shown in Table 3, in Examples 1-1 to 1-16 using the resist underlayer film forming composition (UDL-1 to 16), the dry etching resistance against CF4 gas was significantly improved by the additional treatment of plasma irradiation. The resist underlayer film forming composition used in Examples 1-1 to 1-16, which are examples of the present invention, does not contain a hydroxyl group or an organic group represented by the above general formula (1) in the repeating unit of the polymer, so that the carbon bonds of the resist underlayer film precursor film are easily dissociated and recombined by plasma irradiation to reconstruct it as a resist underlayer film, which is a cured film having a diamond-like carbon structure, and it is considered that it showed excellent dry etching resistance. On the other hand, the improvement in dry etching resistance by the additional treatment of Comparative Examples UDL-1 to 6 was small, being 10 nm / min or less. Since the comparative examples UDL-1 to -6 contain a hydroxyl group or an organic group represented by the above general formula (1) in the repeating unit of the polymer, not only the dissociation and recombination of carbon bonds but also crosslinking reactions occur competitively, which is presumably why the film modification by plasma exposure did not proceed sufficiently.

[0277] UDL-5 contains hydroxyl groups in the terminal structure of the polymer, but does not contain hydroxyl groups in the repeating units of the polymer. Therefore, it is presumed that the dissociation and recombination of carbon bonds proceeds during plasma exposure without being inhibited by the crosslinking reaction, thereby modifying the film to one that exhibits excellent dry etching resistance.

[0278] [Example 2 and Comparative Example 2: Evaluation of filling characteristics] The above resist underlayer film forming compositions (UDL-1 to 16 and comparative UDL-1 to 6) were each applied onto a SiO2 wafer substrate having a dense line & space pattern (line width 60 nm, line depth 100 nm, distance between the centers of two adjacent lines (120 nm)). Next, the coating film was baked at 250°C for 60 seconds to form a resist underlayer film precursor film with a thickness of 100 nm. The substrate used was a base substrate 7 (SiO2 wafer substrate) having a dense line & space pattern as shown in Figure 2 (G) (bird's-eye view) and (H) (cross-sectional view). Next, plasma irradiation treatment was performed under the same additional treatment conditions as in the above dry etching resistance evaluation, and the cross-sectional shape of each of the obtained wafer substrates was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd., to confirm whether or not there was a void (air gap) inside the resist underlayer film filling the gap between the lines. The results are shown in Table 4. When a composition for forming a resist underlayer film with poor filling properties is used, voids are generated inside the resist underlayer film that fills the gaps between the lines in this evaluation. When a composition for forming a resist underlayer film with good filling properties is used, a resist underlayer film 8 without voids is filled inside the resist underlayer film that fills the gaps between the lines of a base substrate 7 having a dense line and space pattern, as shown in Figure 2 (I).

[0279] [Table 4]

[0280] As shown in Table 4, the resist underlayer film forming compositions (UDL-1 to 16) used in Example 2 of the present invention were able to fill dense line and space patterns without generating voids even after the additional treatment of plasma irradiation, and were confirmed to have good filling properties. It was also confirmed that there were no problems with filling properties for the comparative examples UDL-1 to 6.

[0281] [Example 3 and Comparative Example 3: Pattern Forming Method] The above resist underlayer film forming compositions (UDL-1 to 16 and Comparative Examples UDL-1 to 6) were applied onto a silicon wafer substrate on which a SiO2 film having a trench pattern (trench width 10 μm, trench depth 0.10 μm) was formed, and baked in air at 250 ° C for 60 seconds to form a resist underlayer film precursor film with a thickness of 100 nm. Thereafter, the same plasma irradiation treatment as in the above dry etching resistance evaluation was performed. A silicon atom-containing resist intermediate layer material (SOG-1) was applied thereon and baked at 220 ° C for 60 seconds to form a resist intermediate layer film with a thickness of 20 nm, and a single layer resist material for ArF of the resist upper layer film material was applied thereon and baked at 105 ° C for 60 seconds to form a photoresist film with a thickness of 100 nm. A liquid immersion protective film material (TC-1) was applied onto the photoresist film and baked at 90 ° C for 60 seconds to form a protective film with a thickness of 50 nm.

[0282] The silicon-containing resist intermediate layer material (SOG-1) was prepared by the following procedure. The polymer represented by ArF silicon-containing intermediate film polymer (SiP1) and the crosslinking catalyst (CAT1) were dissolved in propylene glycol monoethyl ether as an organic solvent containing 0.1 mass % of FC-4430 (manufactured by Sumitomo 3M Limited) in the ratio shown in Table 5. The obtained solution was filtered through a fluorine resin filter with a pore size of 0.1 μm to prepare the silicon-containing resist intermediate layer material (SOG-1).

[0283] [Table 5]

[0284] The structural formulae of the ArF silicon-containing intermediate film polymer (SiP1) and crosslinking catalyst (CAT1) used are shown below.

[0285] [ka]

[0286] The resist top layer film material (ArF single layer resist material) was prepared by the following procedure. The polymer (RP1), acid generator (PAG1) and basic compound (Amine1) were dissolved in propylene glycol monoethyl ether acetate (PGMEA) as a solvent containing 0.1 mass% of surfactant FC-4430 (manufactured by Sumitomo 3M Limited) in the ratios shown in Table 6. Next, the resulting solution was filtered through a 0.1 μm fluororesin filter. In this way, the ArF single layer resist material was prepared.

[0287] [Table 6]

[0288] The polymer (RP1), acid generator (PAG1), and basic compound (Amine1) used in the resist top layer material (ArF single layer resist material) are shown below.

[0289] [ka]

[0290] The immersion protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent in the ratio shown in Table 7, and filtering through a 0.1 μm fluororesin filter.

[0291] [Table 7]

[0292] The polymer (PP1) used in the immersion protective film material (TC-1) is shown below. [ka]

[0293] Next, the resist upper layer film was subjected to pattern exposure using an ArF immersion exposure apparatus (Nikon Corporation; NSR-S610C, NA 1.30, σ 0.98 / 0.78, 35 degree dipole s-polarized illumination, 6% halftone phase shift mask). It was then baked (PEB) at 100°C for 60 seconds and developed with a 2.38 mass% tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds. This resulted in a 45 nm 1:1 positive line and space pattern (resist pattern).

[0294] Next, using the resist pattern as a mask, the silicon atom-containing resist intermediate layer material (SOG-1) was etched by dry etching using a Tokyo Electron etching device Telius to form a hard mask pattern (SOG-1 pattern).

[0295] Next, the resist underlayer film was etched using the obtained SOG-1 pattern as a mask to form a resist underlayer film pattern.

[0296] Then, the SiO2 film was etched using the resist underlayer film pattern as a mask under the following etching conditions.

[0297] Transfer conditions of resist pattern to silicon-containing resist intermediate layer material (SOG-1). Chamber pressure: 50mT RF power (top): 500W RF power (bottom): 300W CF4 gas flow rate: 150sccm CHF3 gas flow rate: 50sccm Time: 15sec

[0298] Conditions for transferring the silicon atom-containing resist intermediate layer material (SOG-1) pattern to the resist underlayer film. Chamber pressure: 10mT RF power (top): 1,000W RF power (bottom): 300W CO2 gas flow rate: 320sccm N2 gas flow rate: 80sccm Time: 55sec

[0299] Transfer conditions of resist underlayer film pattern onto SiO2 film. Chamber pressure: 100mT RF power (top): 500W RF power (bottom): 300W CF4 gas flow rate: 150sccm CHF3 gas flow rate: 30sccm O2 gas flow rate: 10sccm Time: 130sec

[0300] The cross section of the pattern formed on the SiO2 film was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. The results are shown in Table 8.

[0301] [Table 8]

[0302] As shown in Table 8, in Examples 3-1 to 3-16 in which a resist underlayer film was formed by the resist underlayer film forming method of the present invention using any of the resist underlayer film forming compositions (UDL-1 to 16), the resist upper layer film pattern was finally transferred to the substrate well in each case, and it was confirmed that the resist underlayer film forming method of the present invention is preferably used for fine processing by the multilayer resist method. On the other hand, in Comparative Examples 3-1 to 3-6 in which Comparative Examples UDL-1 to 6, which were confirmed to have insufficient etching resistance compared to the resist underlayer film forming method of the present invention in the above etching resistance evaluation, were used, the pattern shape after substrate transfer etching was vertical, but deterioration of LWR was observed after substrate processing.

[0303] From the above, it has become clear that the resist underlayer film forming method of the present invention is extremely useful for the next generation of microfabrication processes because it is possible to form a resist underlayer film that exhibits excellent dry etching resistance during substrate processing by plasma irradiation. In addition, it has become clear that the pattern forming method of the present invention using this method can form a fine pattern with high accuracy even if the substrate to be processed has steps.

[0304] The present specification includes the following aspects. [1] A method for forming a resist underlayer film on a substrate, comprising the steps of: (i) coating the substrate with a composition for forming a resist underlayer film, the composition including (A) a polymer and an organic solvent, to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. or more and 800° C. or less for 10 to 7,200 seconds to harden the coating film, thereby forming an underlayer film precursor film; (ii) curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film; Including, A method for forming a resist underlayer film, comprising using, as the polymer (A), an aromatic ring-containing resin that does not contain a hydroxyl group or an organic group represented by the following general formula (1) in the repeating units constituting the polymer: [ka] (In the above general formula (1), p is 0 or 1, and * is a bond.) [2] The method for forming a resist underlayer film according to [1], wherein the aromatic ring-containing resin is the polymer (A) having a structure selected from the group consisting of structures represented by the following formula (1-1): [ka] [3] The method for forming a resist underlayer film according to [1] or [2], wherein the polymer (A) has any one of structural units represented by the following general formulas (A-1), (A-2), (A-3), (A-4) and (A-5): [ka] (In the general formula (A-1), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1) above.) [ka] (In the general formula (A-2), Ar1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1), and Ar2 is a fused aromatic ring different from Ar1, and is an unsubstituted fused aromatic ring or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1).) [ka] (In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.) [ka] (In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms.) [ka] (In the general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms that does not contain a hydroxyl group or an organic group represented by the general formula (1), and each of Ar3 and Ar4 represents an unsubstituted benzene ring or naphthalene ring.) [4] The method for forming a resist underlayer film according to any one of [1] to [3], wherein the (A) polymer has a molecular weight of 300 to 5,000 in terms of polystyrene as determined by gel permeation chromatography. [5] The composition for forming a resist underlayer film further comprises: (C) a crosslinking agent, (D) a surfactant, (E) an acid generator, and (F) Plasticizer The method for forming a resist underlayer film according to any one of [1] to [4], wherein the resist underlayer film contains one or more of the following: [6] The method for forming a resist underlayer film according to [5], wherein the crosslinking agent (C) has a structure represented by the following general formula (C-1): [ka] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2).) [ka] [7] The method for forming a resist underlayer film according to any one of [1] to [6], wherein in the step (ii), the plasma irradiation is carried out in an atmosphere of N2, NF3, H2, a fluorocarbon, a rare gas, or a mixture of any of these. [8] The method for forming a resist underlayer film according to any one of [1] to [7], wherein in the step (i), the heat treatment is carried out in an atmosphere having an oxygen concentration of 1% or more and 21% or less. [9] The method for forming a resist underlayer film according to any one of [1] to [7], wherein in the step (i), the heat treatment is carried out in an atmosphere having an oxygen concentration of less than 1%.

[10] A method for forming a pattern on a workpiece substrate, comprising: (I-1) A step of forming a resist underlayer film on a substrate to be processed by the method for forming a resist underlayer film according to any one of [1] to [9]; (I-2) forming a resist intermediate film on the resist underlayer film; (I-3) forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern has been transferred as a mask; and (I-7) A step of processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed. A pattern forming method comprising the steps of:

[0305] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]

[0306] 1... supporting substrate, 1A... substrate to be processed, 2... layer to be processed, 2a... pattern (pattern formed on layer to be processed), 3... resist underlayer film, 3a... resist underlayer film pattern, 4... resist intermediate film, 4a... resist intermediate film pattern, 5... resist upper layer film, 5a... resist upper layer film pattern, 6... exposed portion, 7... underlying substrate having dense lines and spaces, 8... resist underlayer film.

Claims

1. A method for forming a resist underlayer film on a substrate, comprising the steps of: (i) coating the substrate with a composition for forming a resist underlayer film, the composition including (A) a polymer and an organic solvent, to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. or more and 800° C. or less for 10 to 7,200 seconds to harden the coating film, thereby forming an underlayer film precursor film; (ii) curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film; Including, A method for forming a resist underlayer film, comprising using, as the polymer (A), an aromatic ring-containing resin that does not contain a hydroxyl group and an organic group represented by the following general formula (1) in a repeating unit constituting the polymer: 【Chemistry 1】 (In the above general formula (1), p is 0 or 1, and * is a bond.)

2. The method for forming a resist underlayer film according to claim 1, wherein the aromatic ring-containing resin is the polymer (A) containing a structure selected from the group consisting of structures represented by the following formula (1-1): 【Chemistry 2】

3. The method for forming a resist underlayer film according to claim 1, wherein the polymer (A) has any one of structural units represented by the following general formulas (A-1), (A-2), (A-3), (A-4) and (A-5): 【Chemistry 3】 (In the above general formula (A-1), Ar 1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms that does not contain a hydroxyl group or an organic group represented by the above general formula (1). 【Chemistry 4】 (In the above general formula (A-2), Ar 1 is an unsubstituted fused aromatic ring or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the general formula (1), and Ar 2 is Ar 1 and is a fused aromatic ring different from the above, which is an unsubstituted fused aromatic ring or a fused aromatic ring containing, as a substituent, a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group or an organic group represented by the above general formula (1). 【Chemistry 5】 (In the above general formula (A-3), R 1 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms. 【Chemistry 6】 (In the above general formula (A-4), R 2 is any one of a hydrogen atom, a halogen atom, and a linear, branched, or cyclic hydrocarbon group having 1 to 20 carbon atoms. 【Chemistry 7】 (In the above general formula (A-5), R 1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms that does not contain a hydroxyl group or an organic group represented by the above general formula (1), and each of Ar3 and Ar4 is an unsubstituted benzene ring or naphthalene ring.

4. 2. The method for forming a resist underlayer film according to claim 1, wherein the polymer (A) has a molecular weight of 300 to 5,000 in terms of polystyrene as determined by gel permeation chromatography.

5. The composition for forming a resist underlayer film further comprises (C) a crosslinking agent, (D) a surfactant, (E) an acid generator, and (F) Plasticizer 2. The method for forming a resist underlayer film according to claim 1, wherein the resist underlayer film contains one or more of the following:

6. The method for forming a resist underlayer film according to claim 5, wherein the crosslinking agent (C) has a structure represented by the following general formula (C-1): 【Chemistry 8】 (In the above general formula (C-1), W 1 and W 2 each represents a benzene ring or a naphthalene ring which may have a substituent, R 2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2): 【Chemistry 9】

7. In the step (ii), the plasma irradiation is performed using N 2 , N.F. 3 , H 2 2. The method for forming a resist underlayer film according to claim 1, wherein the method is carried out in an atmosphere of a fluorocarbon, a rare gas, or a mixture of any of these.

8. 8. The method for forming a resist underlayer film according to claim 1, wherein in the step (i), the heat treatment is carried out in an atmosphere having an oxygen concentration of 1% or more and 21% or less.

9. 8. The method for forming a resist underlayer film according to claim 1, wherein in the step (i), the heat treatment is carried out in an atmosphere having an oxygen concentration of less than 1%.

10. A method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) A step of forming a resist underlayer film on a substrate to be processed by the method for forming a resist underlayer film according to any one of claims 1 to 7; (I-2) forming a resist intermediate film on the resist underlayer film; (I-3) forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern has been transferred as a mask; and (I-7) A step of processing the substrate to be processed using the resist underlayer film on which the pattern has been formed as a mask to form a pattern on the substrate to be processed. A pattern forming method comprising the steps of:

Citation Information

Patent Citations

  • Pattern forming method, and material for forming underlayer film

    JP2004205685A

  • Compound for forming organic film, composition for forming organic film, method for forming organic film, and patterning process

    JP2017119671A

  • Method for manufacturing cured film and use of the same

    JP2020183506A

Cited By

  • Underlayer film-forming composition for metal-containing resist film and method for producing semiconductor substrate

    WO2026163813A1

  • Plasma-treated silicon-containing resist underlayer film, composition for forming silicon-containing resist underlayer film, and laminate

    WO2026191803A1